Assessment of awareness and knowledge of schistosomiasis among school-aged children (6–13 years) in the Okavango Delta, Botswana - Kebabonye P. Gabaake; Nthabiseng A. Phaladze; Don Eliseo Lucero-Prisno III; Olekae T. Thakadu (Global Health Research and Policy, 2022)
Abstract Background Schistosomiasis is a global health problem affecting 250 million people, with 90% in Sub-Saharan Africa. In Botswana, the burden is high in the Okavango delta because of the water channels. WHO recommends integrated measures, including access to clean water, sanitation, health education, and drugs to control and eliminate schistosomiasis. Gauging knowledge and awareness of schistosomiasis for School-Aged Children (SAC) is crucial. Our study aimed at assessing knowledge and awareness of schistosomiasis among SAC in the Okavango Delta. Methods A cross-sectional survey assessing awareness and knowledge of schistosomiasis in schools was conducted. 480 questionnaires were administered to gather demographic profiles, awareness, and knowledge of risky behaviors. Chi-square and descriptive analysis determined the differences in SAC`s awareness and knowledge levels based on localities, gender, age, and health education. Results The results showed a low awareness level, with only (42%) of respondents having heard about the disease and (52%) knowing its local name. Younger children from Sekondomboro (83%) and Samochima lacked awareness, while children from Mohembo (77%) and those who had health education (70%) demonstrated significant awareness levels (P ≤ 0.001). Seventy-two percent (72%) lacked knowledge of the cause and (95%) did not know the disease life-cycle. Children from Xakao (91%), (85%) Sepopa, and (75%) of younger children did not know haematuria is a symptom of the disease. Older and SAC with health education were more likely to know that swimming is a risk factor (P ≤ 0.001) and (P ≤ 0.05) respectively. Conclusions Although respondents from four schools demonstrated some level of awareness of the disease, and knowledge of risky behaviors, the study showed a lack of in-depth knowledge on the life-cycle and cause of the diseases. We, therefore, recommend the implementation of an integrated approach to health education and improvement in access to clean water and sanitation in all study areas.